Pelaksanaan Program Tahfidz di Pesantren Diniyyah Puteri Padang Panjang: Studi Kualitatif - Rusmani Rusmani; Septi Madeni; Arif Miboy (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Memorizing the Qur’an is a process, as the material to be memorized must be perfect, because this knowledge is studied to be memorized, not to be understood. However, once the memorization of the Qur’an is complete, it is then required to understand the contents contained within it. The purpose of this study is to find out how the tahfidz program is implemented at Pesantren Diniyyah Puteri Padang Panjang. By using a qualitative descriptive research method, it means that the data collected is not in the form of numbers but comes from interviews, field notes, and pictures. To obtain accurate results, this study uses data collection methods in the form of observation, interviews, and documentation. The analysis used includes data reduction, data presentation, and drawing conclusions. The results of this study first show that the Al-Quran tahfidz program at Pesantren Diniyyah Puteri Padang Panjang is a mandatory activity for students in the dormitory and is included in In the extracurricular program at school, the implementation has been running quite well. Second, there are supporting factors from both internal and external sources that facilitate the tahfidz program, such as rewards for students who have reached their memorization targets, designated rooms for students to memorize, and guidance from professional supervisors. The inhibiting factors are: students' laziness due to a packed schedule in both the dormitory and school, and too little time to memorize and review their memorization.